Cellular Imaging With MRI. Issue 5 (October 2016) - Makela, Ashley V.; Murrell, Donna H.; Parkins, Katie M.; Kara, Jenna; Gaudet, Jeffrey M.; Foster, Paula J.
Abstract : Abstract: Cellular magnetic resonance imaging (MRI) is an evolving field of imaging with strong translational and research potential. The ability to detect, track, and quantify cells in vivo and over time allows for studying cellular events related to disease processes and may be used as a biomarker for decisions about treatments and for monitoring responses to treatments. In this review, we discuss methods for labeling cells, various applications for cellular MRI, the existing limitations, strategies to address these shortcomings, and clinical cellular MRI.